Increasing the benefits and sustainability of irrigation through the integration of fisheries: a guide for water planners, managers and engineers - Nguyen-Khoa, S.; McCartney, Matthew P.; Funge-Smith, S.; Smith, L.; Senaratna Sellamuttu, Sonali; Dubois, Mark (Food and Agriculture Organization of the United Nations, 2020)
There is increasing recognition of the need to bring about changes across the full spectrum of agricultural practices to ensure that, in future, food production systems are more diverse, sustainable and resilient. In this context, the objectives of irrigation need to be much more ambitious, shifting away from simply maximizing crop yields to maximizing net benefits across a range of uses of irrigation water, including ecosystems and nature-based solutions. One important way to achieve this is by better integrating fisheries into the planning, design, construction, operation and management of irrigation systems. Irrigation – a major contributor to the Green Revolution – has significantly improved agricultural production worldwide, with consequent benefits for food security, livelihoods and poverty alleviation. Today, irrigated agriculture represents about 21 percent of cultivated land, but contributes approximately 40% of the total global crop production. Many governments continue to invest in irrigation as a cornerstone of food security and rural development. Investments in irrigation often represent a pragmatic form of adaptation to changing climatic conditions. This guide focuses on how to sustainably optimize and broaden the range of benefits from irrigation development - not only economic but also social and environmental benefits. It emphasizes the opportunities that fisheries could provide to increase food production and economic returns, enhance livelihoods and public health outcomes, and maintain key ecosystem services. The guide considers possible trade-offs between irrigation and fisheries, and provides recommendations on how these could be minimized.